The Emerging Concept of Sport-Event-Hosting Strategy: Definition and Comparison. Issue 1 (2nd April 2016) - Chappelet, Jean-Loup; Lee, Kwang Hoon
ABSTRACT: As bidding for the rights to host sport events has become increasingly competitive, more and more countries, regions and cities have been employing public strategies and policies for promoting attractiveness of their locations to host sport events, which can be termed as 'sport-event-hosting strategy' (SEHS). However, from an academic standpoint, minimal effort has been made to conceptualise the notion of SEHS. This paper, thus, attempts to systematically examine such strategy by integrating the main findings of prior theoretical and empirical research. To this end, the paper begins by defining the concept of SEHS and proceeds to examine its constituent elements such as strategic goals, targets, stakeholders, tools, and management process. National variations of SEHS, including the emergence of public hosting policies, are also explored. The conclusion suggests future research directions for SEHS.